Recommended configuration for personal health records by standardized data item sets for diabetes mellitus and associated chronic diseases: A report from Collaborative Initiative by six Japanese Associations. Issue 3 (25th April 2019) - Nakashima, Naoki; Noda, Mitsuhiko; Ueki, Kohjiro; Koga, Tatsuhiko; Hayashi, Michio; Yamazaki, Katsuya; Nakagami, Tomoko; Ohara, Makoto; Gochi, Akira; Matsumura, Yasushi; Kimura, Michio; Ohe, Kazuhiko; et al.
Abstract: It is expected that a large amount of data related to diabetes and other chronic diseases will be generated. However, databases constructed without standardized data item sets can be limited in their usefulness. To address this, the Collaborative Committee of Clinical Informatization in Diabetes Mellitus was established in 2011 by the Japan Diabetes Society and Japan Association for Medical Informatics. The committee has developed core item sets and self‐management item sets for diabetes mellitus, hypertension, dyslipidemia, and chronic kidney disease in collaboration with the Japanese Society of Hypertension, Japan Atherosclerosis Society, Japanese Society of Nephrology, and Japanese Society of Laboratory Medicine, as well as a mapping table that aligns the self‐management item sets with the Japanese standardized codes for laboratory testing. The committee also determined detailed specifications for implementing the four self‐management item sets in personal health record (PHR) applications to facilitate risk stratification, the generation of alerts using information and communications technology systems, the avoidance of data input errors, and the generation of reminders to input the self‐management item set data. The approach developed by the committee may be useful for combining databases for various purposes (such as for clinical studies, patient education, and electronic medical record systems) and for facilitating collaboration between PHR administrators.